2002
DOI: 10.1016/s0893-133x(02)00333-0
|View full text |Cite
|
Sign up to set email alerts
|

Provisional Mapping of Quantitative Trait Loci Modulating the Acoustic Startle Response and Prepulse Inhibition of Acoustic Startle

Abstract: Prepulse inhibition (PPI) of the acoustic startle response (ASR) is a form of sensorimotor gating, defined as an inhibition of the startle response when a low intensityThere is strong evidence that several genes with additive or interactive effects, together with environmental factors, contribute to confer susceptibility to schizophrenia (Carlson and Willott 1996). Given this complexity, one approach to uncover genetic susceptibility factors in schizophrenia has been to search for genes regulating specific end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
59
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 53 publications
5
59
1
Order By: Relevance
“…These strains carry donor A/J chromosomes (chromosomes 2, 16, and 18, respectively) that have previously been suggested to harbor PPI QTL (McCaughran et al 1999;Hitzemann et al 2001;Joober et al 2002). PPI studies of the other substitution strains are being performed as time and resources permit.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These strains carry donor A/J chromosomes (chromosomes 2, 16, and 18, respectively) that have previously been suggested to harbor PPI QTL (McCaughran et al 1999;Hitzemann et al 2001;Joober et al 2002). PPI studies of the other substitution strains are being performed as time and resources permit.…”
Section: Resultsmentioning
confidence: 99%
“…The heritability (h 2 ) of PPI of acoustic startle has been estimated to range from 23 to 67% in inbred mouse strains ( Joober et al 2002;Willott et al 2003), indicating that mapping genes underlying PPI regulation is feasible. Nearly 20 quantitative trait loci (QTL) for PPI have been implicated in mice (McCaughran et al 1999;Hitzemann et al 2001;Joober et al 2002), and 2 PPI loci have been reported in rats (Palmer et al 2003). However, only two murine QTL have been replicated in different studies, and no genes have yet been identified, no doubt due to the unmanageable size of the mapped regions (30 cM).…”
mentioning
confidence: 99%
“…Subtyping schizophrenia A Jablensky 823 205 Prepulse inhibition of the startle reflex [206][207][208] Deficient gating of the auditory evoked response (P50) [209][210][211] P300 amplitude reduction and latency delay 212 N400 amplitude reduction (semantic context underutilization) 213 Mismatch negativity (MMN) [214][215][216][217] Smooth pursuit eye movement dysfunction (SPEM) [218][219][220][221] Antisaccade error rate (AS) [222][223][224] Composite inhibitory phenotype (P50, AS, SPEM) 225 Multivariate electrophysiological endophenotype (MMN, P50, P300, AS) 226 Neuroimaging markers and endophenotypes Fronto-thalamic-cerebellar gray matter deficit 227 Fronto-striato-thalamic gray matter deficit 228 MRI-derived three-factor phenotype 229 MRI whole-brain nonlinear pattern classification 230 Frontal hypoactivation in response to cognitive tasks (hypofrontality) 231 Atrophic and static (neurodevelopmental) schizophrenia endophenotypes 232 Cognitive markers and endophenotypes Continuous performance tests (CPT, signal/noise ratio) [233][234][235] Attention and vigilance-based subtype 18 Verbal dysmnesic subtype 18 Verbal memory deficit, cortical or subcortical type 236,237 Dysexecutive subtype 18 Prefrontal executive/working memory phenotype 238 Frontal/abstraction deficit profile 239 Spatial working memory 240...…”
Section: Molecular Psychiatrymentioning
confidence: 99%
“…PPI deficits are being used successfully in a number of important lines of investigation, from the development of novel antipsychotic agents (Swerdlow et al, 1994;Mansbach et al, 1998;cf Swerdlow and Geyer, 1998;cf Geyer et al, 2001) to the identification of vulnerability genes for schizophrenia (Joober et al, 2002;cf Braff and Freedman, 2002). These efforts would benefit greatly from a map of the neural circuit regulation of PPI in humans, which could guide the search for functional targets of therapeutic drugs and candidate genes.…”
Section: Introductionmentioning
confidence: 99%